Analisis Pengendalian Kualitas Menggunakan Metode Statistical Quality Control(SQC) di PT XYZ - Carisa Ardelia, Dhea; Wahyudin, Wahyudin (UNISTEK, 2026)
Quality control is a crucial aspect of the manufacturing industry to ensure product conformity with standards and to reduce the defect rate. This study aims to analyze quality control on Weld and Nut products at PT XYZ using the Statistical Quality Control(SQC) method with the Seven Tools approach. This includes the use of tools such as check sheets, histograms, scatter diagrams, control charts, Pareto diagrams, stratification, and fishbone diagrams. The data analyzed covered production from November 2024 to January 2025, with a total of 8,478,678 parts produced and 428 defective products identified. The analysis revealed that the dominant types of defects were kizu, kashiri, burry, and dia out spec. Control chart and Pareto analysis indicated that human and machine factors were the primary causes of product non-conformities. Improvement recommendations include enhanced process supervision, operator training, and machine setting adjustments. The application of the SQC method effectively identified root causes and provided concrete recommendations to improve product quality at PT XYZ.